Agama dan Kemajuan Teknologi Digital: Digital Religion dan Media Sosial - Najiha, Rina (Mozaic: Islamic Studies Journal, 2025)
The development of digital technology has globally transformed religious practices, including in Indonesia, by creating a hybrid space between online and offline activities known as digital religion. This study aims to analyze how the transformation of religious practices through social media affects the understanding, practice, and religious identity, particularly among young Indonesian Muslims. Using a literature review method and qualitative content analysis, this research examines various theoretical and empirical references related to digital religion, employing a conceptual framework that integrates the theories of networked religion (Campbell) and mediatization (Hjarvard). The findings show that social media has become a key platform in transforming religious practices, giving rise to new forms of religious authority such as "celebrity preachers" (ustadz selebgram), while also fostering hybrid religious identities that blend tradition with personal interpretation. Religious organizations like NU and Muhammadiyah have successfully adapted by utilizing digital platforms, while pesantrens (Islamic boarding schools) have begun integrating digital literacy into their curricula. However, the study also identifies challenges such as the superficiality of religious understanding due to viral content and the potential for radicalization through social media algorithms. Theoretically, these findings enrich the understanding of digital religion by emphasizing the dimension of locality, while practically, they suggest the need for the development of digital religious literacy and adaptive communication strategies for religious institutions. The study concludes that digital religion in Indonesia creates a new space for negotiation between tradition and modernity, requiring a thoughtful approach to ensure that technological transformation deepens rather than diminishes spirituality.